Investasi Tabungan di Bank Syariah dalam Perspektif Hukum Ekonomi Syariah - Amalia, Feby Ayu (ASY SYAR'IYYAH: JURNAL ILMU SYARI'AH DAN PERBANKAN ISLAM, 2019)
Investment is a commitment to the activities undertaken by a person or legal entity, to set aside a portion of his income in order to be used to conduct a business with the hope at a certain time will get the results (profit). The rise of investment fraud, and the lack of clarity on the returns to profits derived from the investment returns halal or not, require the public to be more selective in investing their wealth. This article discusses the concept of investment and savings investment in Sharia Bank with the sharia economic law perspective. Islamic banking undertakes the business of fund raising, based on Sharia Principles. One of Sharia Bank's investment products is a savings whose investment is based on wadi'ah contract and investment fund based on mudharabah contract or other contract which is not contrary to sharia principles. The regulation of savings in a Sharia Bank is regulated by Law No. 21 of 2008, and Fatwa DSN No: 02 / DSN-MUI / IV / 2000. The law of investing in Sharia Banks is permissible, because by investing in Sharia Banks slowly we can help the equity of economy and economic welfare.